PENGARUH TERPAAN MUSIK PERLAWANAN BAND SUKATANI DAN AFILIASI POLITIK TERHADAP SIKAP POLITIK - Almirah Azaria; Lintang Ratri Rahmiaji (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
Protest music is a form of popular culture that not only provides entertainment but also serves as a tool for political communication. It can influence how people understand and evaluate the social and political situations around them. Sukatani, an Indonesian post-punk band, is known for its lyrics that criticize social injustice, the misuse of power, and government policies. On the other hand, political orientation, as a psychological influence, also shapes how individuals perceive and evaluate political issues. This study aims to understand how the influence of resistance music by the band Sukatani, as well as political affiliation, affects the political attitudes of Generation Z. The study is grounded in Social Cognitive Theory and the Funnel of Causality Theory. The study employed a quantitative method using simple linear regression analysis to examine the effect of the independent variable exposure to Sukatani Band's protest music on the dependent variable of political attitudes, as well as the effect of the independent variable of political affiliation on the dependent variable of political attitudes. The findings of this study indicate that the influence of the coverage to Sukatani Band's protest music and an individual's political affiliation positively and significantly influence the political attitudes of Generation Z. The influence of coverage by protest music accounts for 20.2%, while political affiliation contributes 19.1% to shaping an individual's political attitudes. These findings also objectively demonstrate that the greater the exposure to Sukatani Band's protest music and the stronger an individual's political affiliation with the opposition, the more critical Generation Z's political attitudes toward government policies become.